Creating a Safe Learning Environment for the English Class Through Project Work (2020)
ABSTRACT: This paper reports the results of an action research project which aimed at creating a safe learning environment through the implementation of a project work unit focused on students’ realities. The participants of this project were fifth graders at a public institution located in the rural area of Rionegro, Antioquia. Data collected for this study included teacher journals and students’ artifacts. Additionally, due to local and national measures adopted during the COVID-19 crisis, the data included family involvement. The findings showed that the inclusion of learners’ realities, the way teachers mediate relationships and the quality of parental involvement foster a positive and collaborative learning environment which also affects positively students’ academic achievement.